MODEL EVALUASI PEMBELAJARAN DALAM PENDIDIKAN ISLAM: ANALISIS MODEL CIPP, KIRKPATRICK, DAN SCRIVEN - Nora, Syovia; Julhadi, Julhadi (Ensiklopedia of Journal, 2026)
Learning evaluation is a crucial component of the educational process as it functions to assess the achievement of learning objectives and serves as a basis for continuous improvement. In the context of Islamic Religious Education, learning evaluation is not only directed at cognitive achievement but also encompasses affective and psychomotor domains. This article aims to comprehensively examine and analyze learning evaluation models, particularly the CIPP, Kirkpatrick, and Scriven models, and their relevance to Islamic Religious Education. This study employed a qualitative approach using library research. Data were collected from books, scholarly journal articles, and academic documents related to learning evaluation models. Data analysis was conducted using a descriptive-analytical method by examining the concepts, characteristics, strengths, and limitations of each evaluation model. The findings indicate that the CIPP model emphasizes comprehensive evaluation of context, input, process, and product; the Kirkpatrick model focuses on a four-level evaluation ranging from reaction to results; while the Scriven model highlights formative and summative evaluation conducted independently of predetermined objectives. These three models have distinct strengths and can be adapted in Islamic Religious Education to enhance the quality of learning processes and outcomes.Keywords: learning evaluation; CIPP model; Kirkpatrick model; Scriven model; Islamic education